Green synthesis of imidazo[1, 2-a]pyridines using calix[6]arene-SO3H surfactant in water. Issue 25 (20th June 2018) - Esmaielzade Rostami, Mahshid; Gorji, Banafsheh; Zadmard, Reza
Graphical abstract: Highlights: Synthesis of imidazo[1, 2- a ]pyridines in water. Using of sulfonated calix[4]arene and calix[6]arene as a reusable catalyst. Simple procedure, short reaction time with good yield. Abstract: In this research, green synthesis of imidazo[1, 2- a ]pyridines in the presence of calix[ n ]arenes-SO3 H as a Brønsted acid catalyst and surfactant is described. Using of calix[ n ]arenes in water provided a hydrophobic cavity that successfully carried out the synthesis reactions at short times with high yields. This catalyst system is recoverable with a simple extraction using an organic solvent and reusable for at least for 5 cycles without any losses of its activity.